DESAIN DAN UJI COBA LEMBAR KERJA SISWA DENGAN PENDEKATAN SCAFFOLDING - wahyuni rizka; Lazulva Lazulva (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractThe main objective of the study was to examine the validy and practical level of student work sheet by a valid and practical of scaffolding approach. The study was a developing study by using 4-D (Define, Design, Develop, Disseminate). It was located in Senior High School 1 Kampar and Senior High School 2 Bangkinang City. The participants of the study were the media design expert, learning material expert, and chemistry teacher as a subject and student worksheet in the topic of the balance of chemistry by a scaffolding approach as an object. Data were collected by using a primary data from the questioner. The instruments of the data collection are the validity questioner and practical questioner. The data is analyzed by using Qualitative and Quantitative Descriptive Analysisi Technique. The findings showed the student worksheet have a percentage of validity level of 84.98% (very valid) and practical level of 87% (very practical). It can be identified that the student worksheet is accepted and can be used as a teacher learning material supplement.Keywords: student worksheet, scaffolding, chemistry balance.